A relação dos valores organizacionais declarados e compartilhados - uma percepção entre o real e o desejável: um estudo de caso em uma Instituição EAD de Feira de Santana - Ba - OLIVEIRA, Mennandro Menezes de (2015)
The present research sought to identify whether there is alignment between the shared values and the organizational, perceived by the staff and students in an educational company of the city of Feira de Santana-Bahia. To achieve this goal, as theoretical vision of culture both in the approach of Schein (2004), Hofstede (1991) and Aktouf (1994). The methodology has descriptive, qualitative and quantitative nature. The research aimed to identify, through interviews and document analysis, the perception of the institution about the organizational culture. Completing the qualitative part of this research, we used the focal group. Were held with teachers and administration of the institution. Discussions took place about the culture and perceptions of organizational values declared by IES, as well as those shared by the participants. For the analysis of data collected, both for the interviews and documentary analysis and focus group was used to discourse analysis in the perspective of Fiorin (2008). In step a quantitative field research with the use of a questionnaire among the students. For the analysis of the data collected was used the descriptive statistics. The data were collected between the months of May to November 2015. These indicate an alignment of documents analyzed, the speeches of the top management and the interviews between the teachers and the administrative staff. In qualitative research indicated that these cultural values desired by top management are fully shared by other members of the IES, where values such as: quality, interaction, communication, and transparency are perceived with greater levels of agreement by respondents, which indicates a high share of organizational values within the IES. Finally, the quantitative research data indicate that there is an important relationship between the perception of the cultural values present in the institutions of higher education on the part of academics, indicating that there is a lack of sharing of the values disseminated by senior management on the part of these actors.